“Reading the Mind in the Eyes Test”: Translated and Korean Versions - Koo, Se Jun (Psychiatry Investig, 2021)
OBJECTIVE: The Reading the Mind in the Eyes Test (RMET) was developed by using Caucasian eyes, which may not be appropriate to be used in Korean. The aims of the present study were 1) to develop a Korean version of the RMET (K-RMET) by using Korean eye stimuli and 2) to examine the psychometric properties of the Korean-translated version of the RMET and the K-RMET. METHODS: Thirty-six photographs of Korean eyes were selected. A total of 196 (101 females) healthy subjects were asked to take the Korean-translated version of the RMET and K-RMET. To assess internal consistency reliability, Cronbach’s alpha coefficients were computed, and test–retest reliability was assessed by the intraclass correlation coefficient (ICC) and Bland-Altman plots. Confirmatory factor analysis (CFA) and item analysis were also conducted. RESULTS: Internal consistency, measured by Cronbach’s alpha, was 0.542 for the Korean-translated version of the RMET, and 0.540 for the K-RMET. Test–retest reliability (n=25), measured by the ICC, was 0.787 for the Korean-translated version of the RMET, and 0.758 for the K-RMET. In CFA, the assumed single and 3-factor model fit indices were not good in the both types of RMETs. There was difficulty in discrimination in nine items of the Korean-translated version of the RMET and 10 items of the K-RMET. CONCLUSION: The psychometric properties of both the Korean-translated version of the RMET and the K-RMET are acceptable. Both tests are applicable to the clinical population, as well as the general population in Korea.